Bidirectional transmittance of transparent windows with external or backside condensation of nonabsorbing cap-shaped droplets. (August 2020) - Huang, Yong; Feng, Chenxi; Hoeniges, Jack; Zhu, Keyong; Pilon, Laurent
Highlights: Systematic study of bidirectional transmittance of windows with droplets on its front or back. Transmittance was independent of droplet size distribution and spatial arrangement. Transmitted photons were concentrated in angular region bounded by cutoff angles. Analytical expressions of cutoff angles agreed well with numerical simulations. Bidirectional transmittance away from incident direction increased with surface area coverage. Abstract: This study investigates systematically the effects of nonabsorbing droplets on the bidirectional transmittance of transparent windows. The Monte Carlo ray-tracing method was used to predict the bidirectional transmittance of transparent windows supporting monodisperse or polydisperse and randomly distributed droplets on their front side or backside. In both cases, photons that did not interact with the droplets were transmitted in the same direction as the incident direction. In addition, the bidirectional transmittance was found to be independent of the diameter and size distribution of the nonabsorbing droplets. It also featured cutoff transmission angles for certain ranges of incident and contact angles for either external or backside droplets. Analytical predictions of these cutoff angles were developed and were in excellent agreement with results from numerical simulations. Moreover, the bidirectional transmittance of the windows with either front or back side droplets increased with increasing projected surface area coverage at transmission angles other than the incident angle. The hemispherical distributions of the bidirectional transmittance showed that the photons scattered into other transmission azimuthal angle were concentrated in the angular region bounded by the cutoff angles for either external droplets or backside droplets.